2014
DOI: 10.1124/dmd.114.059105
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Impact of Substrate Selection on In Vitro Organic Anion Transporting Polypeptide 1B1 Inhibition Profiles for the Prediction of Drug-Drug Interactions

Abstract: The risk assessment of organic anion transporting polypeptide (OATP) 1B1-mediated drug-drug interactions (DDIs) is an indispensable part of drug development. We previously reported that in vitro inhibitory potencies of several inhibitors on OATP1B1 depend on the substrates when prototypical substrates, estradiol-17b-glucuronide (E 2 G), estrone-3-sulfate, and sulfobromophthalein were used as test substrates. The purpose of this study was to comprehensively investigate this substrate-dependent inhibition of OAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
141
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(160 citation statements)
references
References 45 publications
18
141
1
Order By: Relevance
“…In hindsight, the inhibitory effects of FA against OATP isoforms with potency comparable to established inhibitors (Izumi et al, 2015) are not altogether surprising. FA contains a lipophilic [molecular weight = 516.7, calculated topological surface area = 104 Å 2 , calculated LogP = 7.28, LogD (pH 7.4) = 2.66] steroidal nucleus with a carboxylic acid (pK a = 5.7) group (Turnidge, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In hindsight, the inhibitory effects of FA against OATP isoforms with potency comparable to established inhibitors (Izumi et al, 2015) are not altogether surprising. FA contains a lipophilic [molecular weight = 516.7, calculated topological surface area = 104 Å 2 , calculated LogP = 7.28, LogD (pH 7.4) = 2.66] steroidal nucleus with a carboxylic acid (pK a = 5.7) group (Turnidge, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Such a study would confirm the critical role BCRP plays in rosuvastatin absorption by evaluating, through DDI, the impact solitary inhibition of BCRP has on statin exposure. Although rosuvastatin was not used as the in vitro probe to assess OATP1B1 and BCRP inhibition potential, estradiol 17b-glucuronide is a surrogate for OATP1B1-mediated rosuvastatin transport (Izumi et al, 2015), and for BCRP, even if a fostamatinib IC 50 value using rosuvastatin was 100-fold higher than that obtained versus estrone 3-sulfate, it would not change DDI potential or predictions. The data reproduced from the clinical interaction study by Martin et al (2016) demonstrated that sole inhibition of BCRP by fostamatinib resulted in a clinically significant approximately 2-fold increase in rosuvastatin exposure (AUC and C max ).…”
Section: Discussionmentioning
confidence: 99%
“…F a and F g were set to 1 (Ito et al, 1998). Plasma concentration-time profiles of a single oral dose of 600 mg rifampicin, 200 mg trimethoprim, and 300 mg clopidogrel were obtained from our clinical study and that of a single oral dose of 600 mg gemfibrozil was obtained from reported data (Honkalammi et al, 2011a Izumi et al, 2015). The quantitative prediction of the OATP1B1-mediated DDIs by PBPK model needs to be performed by using the inhibition data obtained with a clinically relevant probe (e.g., pitavastatin, pravastatin…), because the inhibition of OATP1B1 is substrate dependent (Izumi et al, 2015).…”
Section: Methodsmentioning
confidence: 99%